Coupled Thermal Stress Analysis of Volvo Truck Disc Brake - Welteji Bena; Goftila Sirata (Advances in Materials Science and Engineering)
This paper deals with the coupled thermal structural analysis developed in Volvo heavy truck disc brake as a function of disc thickness and braking time. A ventilated type of disc brake was employed by having vents (holes) on its surface, which needs a cooling system. When the brake pedal is applied, the friction between the disc and pad tremendously increases due to the heat generated in this system. This heat was partitioned into two contacting bodies (disc rotor and pad). Both analytical and numerical approaches were used to carry out the analysis. Analytically, the transient temperature obtained by the partial solution approach and the stress field were evaluated by the elastic von Mises criterion. In the numerical approach, temperature and stress response were analyzed by the explicit standard ABAQUS. From both results, high thermal gradient and von Mises stress distribution were observed at the sharp edges of the disc, which causes a decrement in braking efficiency and an overall drop in braking performance.